Improved Prediction of Endoxifen Metabolism by CYP2D6 Genotype in Breast Cancer Patients Treated with Tamoxifen - Schroth, Werner; Winter, Stefan; Mürdter, Thomas; Schaeffeler, Elke; Eccles, Diana; Eccles, Bryony; Chowbay, Balram; Khor, Chiea C.; Tfayli, Arafat; Zgheib, Nathalie K.; Eichelbaum, Michel; Schwab, Matthias; et al. (Frontiers in Pharmacology, 2017)
Purpose: Prediction of impaired tamoxifen (TAM) to endoxifen metabolism may be relevant to improve breast cancer treatment, e.g. via TAM dose increase. The polymorphic cytochrome P450 2D6 (CYP2D6) strongly determines an individual’s capacity for endoxifen formation, however CYP2D6 phenotype assignments inferred from genotype widely differ between studies. Thus, we modeled plasma endoxifen predictability depending on variable CYP2D6 genotype groupings. Methods: CYP2D6 diplotype and metabolite plasma concentrations were assessed in 908 pre- and postmenopausal estrogen receptor (ER)-positive, TAM treated early breast cancer patients of Caucasian (N=678), Middle-Eastern Arab (N=77) and Asian (N=153) origin. Robust coefficients of determination (R2) were estimated for endoxifen (E) or metabolic ratio endoxifen/desmethyl-TAM (E/DMT) as dependent and different CYP2D6 phenotype assignments as independent variables. Allele activity scores (AS) were modified with respect to a reduced *10 allele activity. Predictability of endoxifen plasma concentrations above the clinical threshold of 5.9 ng/mL was investigated by receiver operating characteristic (ROC) analysis. Results: CYP2D6 diplotypes (N=898) were strongly associated with E and E/DMT independent of age (P < 10-15). Across all ethnicities, 68-82% inter-patient variability of E/DMT was explained by CYP2D6 diplotype, while plasma endoxifen was predictable by 39-58%. The previously used codeine specific phenotype classification showed worse prediction for both endpoints particularly in Asians (median R2 <20%; P < 10-9). Downgrading of *10 activity slightly improved the explanatory value of metabolizer phenotype (P < 0.002). Endoxifen plasma concentrations above the clinical threshold of 5.9 ng/mL were achieved in 82.3% of patients and were predictable (96% sensitivity, 57% specificity) by CYP2D6 diplotypes with AS > 0.5, i.e. omitting PM/PM and PM/IM patients. Conclusions: The CYP2D6 explanatory power for active drug level assessment is maximized by TAM-specific phenotype assignments while a genotype cutoff that separates PM/PM and PM/IM from the remaining patients may improve clinical benefit via increased endoxifen concentrations.